Magnetic Reynolds Number and Neon Current Sheet Structure in the Axial Phase of a Plasma Focus - Lee, S.; Saw, S. H.; Lee, P.; Rawat, R. S.; Devi, K. (Springer US, 2013)
The Magnetic Reynolds Number (MRN) in neon is computed as a function of Neon shock speed. The magnetic field profiles at various positions in the axial run down phase of the INTI Plasma Focus device are measured over a range of pressures from 2 to 20 Torr. These profiles are assessed for good electromagnetic coupling including measuring the current per unit current sheet thickness as a comparative measure of current sheet diffusion. It was found that at an axial current sheet speed of over 3.5 cm/μs (corresponding to MRN > 15), the current sheet has a compact profile with current density of 55 kA/cm of sheet thickness whereas at speeds below 2.8 cm/μs (corresponding to MRN < 10) the profile is more diffuse with current density less than 30 kA/cm of sheet thickness. Based on these studies it is proposed to take a speed of 3 cm/μs corresponding to an MRN of 10 as the minimum speed of neon current sheet below which the electromagnetic coupling begins to weaken.